Republic of Croatia : Second Review Under the Stand-By Arrangement and Requests for Extension and Augmentation of the Arrangement, Rephasing of Purchases, and Waiver of Nonobservance of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2006)
The staff report for the Second Review Under the Stand-By Arrangement (SBA) on the Republic of Croatia highlights fiscal policy and monetary and financial sector policies. The policy implementation under this SBA has yielded sizable fiscal consolidation and advances in structural reforms, despite some snags. The authorities have taken a number of measures to discourage external borrowing, address foreign currency-related credit risk, and strengthen supervision. The health reform aims at improving the financial situation in the sector and rationalizing public spending on health.